Extracorporeal membrane oxygenation for acute pulmonary embolism after postoperative craniocerebral trauma: a case report - Liao, Xiaozu; Chen, Xiaojuan; Zhong, Shi; Wen, Junlin; Li, Binfei (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Massive pulmonary embolism (PE) is a life-threatening complication of major surgery with a mortality rate of up to 50%. Extracorporeal membrane oxygenation (ECMO) is primarily used for respiratory and circulatory support. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) was used to stabilize patients with acute massive PE. Acute brain injury, vascular disease, and immunosuppression, as proposed in the 2021 ELSO guidelines, are contraindications to ECMO. Case summary: We report a case of a patient with craniocerebral trauma whose postoperative course was complicated by massive PE and subsequent cardiac arrest that required emergent VA‐ECMO, followed by anticoagulation with heparin. The patient showed hemodynamic improvement. The patient was discharged 68 days after hospitalization. Discussion: ECMO has gradually been accepted for patients with craniocerebral injuries. The safety and effectiveness of ECMO in patients with craniocerebral injury, as well as the duration of ECMO and anticoagulation strategies, need to be further studied.